An online study of associations between physical activity, cognitive functioning and food choice - Madhronica Sardjoe; Tanja Adam; Guy Plasqui; Sarah Aldred; Colin T. Dourish; Suzanne Higgs (Appetite, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Dominance of indirect effects of deer populations on soil biodiversity - Nida Amin; Colin Brock; Aven Beech; Virginia Morera-Pujol; Adam F. Smith; Simone Ciuti; Tancredi Caruso (European Journal of Soil Biology, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Peter S. Maitland: An obituary - Colin E. Adams; Ian J. Winfield (Journal of Fish Biology, 2026)

Unprecedented Burning in Tropical Peatlands During the 20th Century Compared to the Previous Two Millennia - Yuwan Wang; Ted R. Feldpausch; Graeme T. Swindles; Patrick Moss; Hamish A. McGowan; Thomas G. Sim; Paul J. Morris; Adam Benfield; Colin Courtney‐Mustaphi; David Wahl; Encarni Montoya; Esther Githumbi; et al. (Global Change Biology, 2026)
Tropical peatland wildfire incidence has risen in recent decades, driven by drainage for land use and intensified by severe droughts with global climate change. These disturbances have altered vegetation structure, disrupted ecosystem functioning, and increased carbon emissions, particularly in Southeast Asia. However, the long‐term history and characteristics of wildfires in tropical peatlands remain largely unknown. Here, we compiled fifty‐eight macro‐charcoal records from peatlands across the tropics, ranging from lowland forested to montane peatlands, to assess millennia‐scale changes and controlling factors of tropical peatland burning. We divided the datasets into four main sub‐regions: Neotropical, Afrotropical, Indomalayan and Australasian ecoregions to explore regional variability. Tropical peatlands had high burning levels between 0 and 850 ce , followed by a relatively low and stable period until a marked increase during the 20th century. The general trend in tropical peatland burning follows changes in global temperature, and climate variables that control the length and severity of drought events have a notable influence on peat burning before 1900 ce . During the 20th century, regional differences were observed, with declining fire trends in the Neotropical and Afrotropical regions and increasing fire trends in the Indomalayan and Australasian regions. This difference is likely attributable to human activities, and such intervention is also evident in palm swamps and hardwood swamps under similar wet, weakly seasonal climates. With the increase in anthropogenic pressures on peatlands and greater climate variability, future wildfires in peatlands are likely to become more frequent and widespread across all tropical ecoregions. Conservation and sustainable land‐use practices could be used to mitigate and control peatland burning and protect these carbon‐rich sinks.

Inshore marine coastal zone migration patterns in Atlantic salmon post‐smolts emigrating from eight rivers in north‐east Scotland - Colin E. Adams; Ruaidhri Forrester; Matthew Newton; Angus J. Lothian; Hannele M. Honkanen; Davide Thambithurai; Lorna Wilkie; Melanie A. Smith; Marcus Walters; Richard Miller; Karen Muller; Brian Shaw; et al. (Journal of Fish Biology, 2026)
Atlantic salmon, Salmo salar , migrate through multiple habitat types, each having the potential to impact differently upon migration success. The inshore marine coastal zone is arguably disproportionately impacted by potential stressors on populations. We investigated the migration of Atlantic salmon post‐smolts ( n = 898) from eight rivers (populations) through the inshore marine coastal zone over a 2‐year period using acoustic telemetry. Migration success through marine inlets where fish first entered seawater, and through the wider inshore marine coastal area (the Moray Firth, north‐east Scotland) was consistently high across populations and across years (mean = 77%). There was no evidence of the high inshore marine predation rates reported elsewhere. Post‐smolts utilised well‐defined inshore marine migration pathways that were broadly consistent among populations and over time. The pace of migration through the inshore marine coastal habitat was also consistently rapid across populations and time, with the period of migration being seasonally constrained (mean across population = 36.5; range 18–45 days). Taken together with existing literature, this study suggests that the patterns of migration of Atlantic salmon post‐smolts through the inshore marine coastal zone are likely highly environment specific.

Domain adaptation and computer vision approaches for robust detection of jellyfish in aquaculture - Lukas Folkman; Kylie A. Pitt; Jessica K. Strickland; Adam Smark; Colin Johnston; Maria E. Albinsson; Christine Huynh; Bela Stantic (Aquaculture International, 2026)
Jellyfish blooms pose a significant economic threat to the global aquaculture industry, causing mass mortality events in farmed fish. Automated detection systems are needed for early warning, but existing computer vision models have not been tested in the challenging visual conditions of aquaculture pens. We evaluated domain adaptation approaches and jellyfish object detection models trained specifically for aquaculture environments, comparing eight architectures including convolutional (YOLOv11) and transformer-based (RT-DETR, DINO) models. Our novel dataset comprised 31,875 jellyfish annotations across 2558 images extracted from 118 unique videos recorded in salmon farms in Tasmania, Australia, capturing jellyfish and gelatinous zooplankton under challenging conditions of high turbidity, complex backgrounds, and low visibility. To evaluate domain adaptation strategies, we combined publicly available datasets with two newly collected non-aquaculture datasets, creating a diverse corpus of 17,622 images with 32,025 annotations. Unlike previous studies, we implemented a strict evaluation protocol accounting for spatial–temporal correlations of images extracted from the same video sequence. Detection transformers consistently outperformed fully convolutional architectures. The DINO architecture with a transformer backbone achieved 56.5% mAP 50 when pre-trained on the combined non-aquaculture data and fine-tuned on aquaculture data—a 4.6 percentage point improvement over training on aquaculture data alone—with strongest improvements in detecting challenging categories such as ctenophores (AP 50 improved from 36.9% to 51.3%). This work provides the first jellyfish detection system trained and evaluated for aquaculture environments and demonstrates that transformer-based architectures with large-scale pre-training on out-of-domain data offer the most effective approach for developing jellyfish early warning systems in fish farms.

Wave impacts on vertical cliffs: Insights from laboratory experiments and field observations - Yaxiong Shen; Colin N. Whittaker; Catriona F. Thompson; Alison C. Raby; Adam P. Young; Mark E. Dickson (Coastal Engineering, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Identifying temperature cues driving increased voltinism in a geometrid moth - Jemma Guthrie; Hannele M. Honkanen; Daniel T. Haydon; Colin E. Adams (Oecologia, 2025)
Identifying the environmental cues that determine the timing of developmental processes is vital to understanding the effects of climate change on populations. However, as developmental processes are inherently difficult to measure directly at the population level, the drivers and potential consequences of change in their timings remain unknown in most species. Here we explore the use of long-term monitoring data for assessments of change in the number of generations per year and its impact on abundance, demonstrating new applications for a rapidly growing data source. Data derived from a light trap in west-central Scotland operated over 56 years (1968 to 2023) showed that the small phoenix moth, Ecliptopera silaceata, switched from a univoltine to bivoltine generation pattern. This voltinism change was predicted by an increased minimum temperature in a critical time window towards the later part of the first generation’s flight period. The population shows positive density dependence and the change in voltinism has no significant negative effect on population size, indicating no evidence of a developmental trap that has been postulated for other species. These results identify some of the proximate mechanisms of developmental responses to climate change in general and in voltinism in particular, specifically highlighting the importance of sustained temperature above minimum thresholds for development. These results could also help to make predictions about future changes in population sizes under climate change and increasing voltinism, in addition to how these changes may differ between species.

Defining the water flow cues for navigation in migrating Atlantic salmon smolts - Mikolaj E. Kundegorski; Hannele M. Honkanen; Alastair Stephen; Colin J. Torney; Shaun Killen; Colin E. Adams (Journal of Fish Biology, 2025)
For migratory species, successful navigation is critical to fitness. In Atlantic salmon, for example, there is evidence that during migration from natal streams to the sea, passage through waters with poorly defined or mixed water velocity patterns may constrain directional navigation, causing individuals to become trapped or delayed in lakes or other bodies with slowly flowing water. In this study, we determined the minimum water velocities needed to elicit a behavioural response, in this case a change in the direction of holding position, in both wild origin and domesticated salmon smolts. Smolts required a directional flow in excess of 8.9 cm s −1 to exhibit effective directional orientation towards the current. Smolts of a domesticated farm origin exhibited a similar qualitative and quantitative response as wild fish. These results suggest that, in areas where the downstream migrating Atlantic salmon smolts pass through low‐directional water flow, it may be possible to manipulate directional flows above this minimum threshold, at least temporarily, as a management tool to increase migration success. This is likely to be particularly true where smolts are passing through dams, reservoirs or other impounded waters.

Determinants of riverine migration success by Atlantic salmon ( Salmo salar ) smolts from rivers across the UK and Ireland - Jessica R. Rodger; Jemma Guthrie; Hannele M. Honkanen; Angus J. Lothian; Jessie Lilly; Marcus Walters; Richie Miller; Lorraine Hawkins; Al Reeve; Jamie Ribbens; Jim Henderson; Debbie Parke; et al. (Journal of Fish Biology, 2025)
There is some evidence that the river migration success of Atlantic salmon smolts, on their first migration to sea, varies both spatially and temporally. However, we have only a poor understanding of what may be driving this variation. In this study, we used acoustic telemetry to quantify the spatial and temporal variations in river migration success in Atlantic salmon smolts on their first migration to sea. In total 4120 Atlantic salmon smolts migrating through 22 rivers in Scotland, England, Ireland, and Northern Ireland over multiple years were included in the study. Individuals were defined as successful migrants if detected leaving the river to enter marine waters. The results show significant temporal (up to 4 years) and spatial (river) variations in migration success, with overall between‐river migration success varying from 3.4% to 97.0% and between years from 3.4% and 61.0%. Temporal variation in migration success was river specific, with some rivers being more temporally stable (exhibiting little variation between years) than others. Across all rivers and years, individual migration success was predicted positively by body condition and negatively by tag burden. The rate of migration success for a population (migration success standardized to a common river distance [proportion km −1 ]) was predicted by a number of environmental factors. The proportion of river catchment that comprised wetland and woodland positively predicted migration success, whereas the proportion of grassland and peatland in a catchment negatively predicted the rate of migration success. Although the mechanisms through which these effects may be operating were not directly examined in this study, we discuss some potential routes through which they may occur.

Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

Cytochromes P460 and c′-β: exploiting a novel fold for multiple functions - Hannah R. Adams; Sotaro Fujii; Hans E. Pfalzgraf; Peter Smyth; Colin R. Andrew; Michael A. Hough (JBIC Journal of Biological Inorganic Chemistry, 2025)
Two related classes of ligand-binding heme c -containing proteins with a high degree of structural homology have been identified and characterized over recent decades: cytochromes P460 (cyts P460), defined by an unusual heme-lysine cross-link, and cytochromes c ′-β (cyts c ′-β), containing a canonical c -heme without the lysine cross-link. The shared protein fold of the cyt P460-cyt c ′-β superfamily can accommodate a variety of heme environments with entirely different reactivities. On the one hand, cyts P460 with polar distal pockets have been shown to oxidize NH 2 OH to NO and/or N 2 O via proton-coupled electron transfer. On the other hand, cyts c ′-β with hydrophobic distal pockets have a proposed gas binding function similar to the unrelated, but more extensively characterized, alpha helical cytochromes c ′. Recent studies have also identified ‘halfway house’ proteins (cyts P460 with non-polar heme pockets and cyts c ′-β with polar distal heme pockets) with functions yet to be resolved. Here, we review the structural, spectroscopic and enzymatic properties of the cyt P460-cyt c ′-β superfamily with a view to understanding the structural determinants of their different functional properties. Graphical abstract

Complex landscape, instream and anthropogenic environmental features drive genetic and morphological structuring amongst brown trout (Salmo trutta) populations in a dendritic river system - Jessica R. Rodger; Hannele M. Honkanen; Caroline R. Bradley; Patrick Boylan; Paulo A. Prodöhl; Colin E. Adams (Evolutionary Ecology, 2025)
Untangling the patterns and proximate drivers of intraspecific genetic and phenotypic structuring informs our understanding of the evolutionary processes shaping diversity. This study investigated morphological and genetic structuring of brown trout ( Salmo trutta L.) populations across varying spatial scales in a single, complex, dendritic river catchment and examined the potential natural and anthropogenic environmental features driving this structuring. Morphometric and hierarchical genetic structuring analyses of fish from 22 sampling sites in the River Foyle catchment, Ireland (~ 4500km 2 ) identified 19 morphologically distinct groups and 15 genetically distinct populations, separated by river distances ranging from 0.4 km to 188 km. Isolation by Distance was the main factor shaping both genetic and morphological divergence, indicating that strong philopatry is one of the major drivers of the observed population structuring in this system. However, both natural and anthropogenic environmental variables also explained pairwise genetic and morphological differences between sampling sites. Thus, the pairwise differences in the area of woodland in the upstream catchment, water phosphorus concentration, biological oxygen demand, catchment slope, urban area in upstream catchment, altitude, site specific percentage of canopy cover and dissolved oxygen concentration in the river channel were correlated with genetic divergence. The pairwise differences in the concentration of suspended solids, the extent of bankside overhang, the composition of bedrock, boulder and cobble substrates, watercourse width, catchment slope and site altitude were correlated with between-site morphological differences. We hypothesise that local differential selection pressures comprising both natural environmental variation and variation resulting from anthropogenic effects, in combination with strong philopatry and random genetic processes drive the clearly defined genetic and phenotypic patterns described here.

The effect of downstream translocation on Atlantic salmon Salmo salar smolt outmigration success - Ruaidhri Forrester; Hannele M. Honkanen; Jessie Lilly; Amy Green; Jessica R. Rodger; Brian A. Shields; Philip Ramsden; J. Peter Koene; Melanie Fletcher; Colin W. Bean; Colin E. Adams (Journal of Fish Biology, 2025)
Trap and transport, the capture and subsequent translocation of fish during the freshwater phase of their migration, is becoming more common as a management intervention. Although the technique can be successful, it is costly and can have unintended effects on the fish being transported. This study investigates whether trap and transport can be used to increase the migration success of Atlantic salmon, Salmo salar , smolts in naturally flowing rivers. Seaward‐migrating S. salar ( n = 294) from two UK rivers were tracked using acoustic telemetric techniques. Outmigration success and timing were compared between non‐transported (released at the original in‐river capture site) and transported (released ca. 23 km downstream of the capture site) individuals. Downstream translocation increased the proportion of fish that successfully migrated to marine waters, and there was no indication that transport reduced post‐release survival. The post‐release migration speed of transported fish was slower than expected but this was likely a function of their advanced migration timing rather than an inhibition of their capacity to migrate. These results suggest that trap and transport can increase the outmigration success of S. salar smolts, but the earlier river exit dates of transported fish could negatively affect their survival at sea.

Lake shape and the characteristics of migration behavior modify Atlantic salmon smolt migration success through lakes - Matthew Newton; Joseph McCallum; Hannele M. Honkanen; Alastair Stephen; Jessie M. Lilly; Danielle L. Orrell; Amy Green; Louise Chavarie; Jessica R. Rodger; Colin E. Adams (Journal of Fish Biology, 2025)
Migration is a high‐risk behavior. For the Atlantic salmon, Salmo salar , migrating from its river nursery area to marine feeding grounds, the magnitude of risk varies with habitat type. Passage through lakes, in particular, is associated with low rates of migration success. Downstream migrating salmon smolts are rheotactic when migrating in rivers, but lakes typically provide poorer directional currents for migrating salmon. In this study we tested if, in the absence of clear navigational cues in lakes, Atlantic salmon smolts switch to a random search strategy to find the outflowing river. We constructed random search simulations to test if lake basin shape has an effect on migration success. We also compared simulated migration characteristics with migrations of salmon smolts through five real lakes for which there are telemetry data for migrating salmon. Correlated random walk simulations showed that a random search strategy could be successful for all lake shapes tested but was more successful in curved (round and elliptical) than rectangular basin shapes. Rectangular basins with the migration start and stop points at the ends of the lake had a higher success than those where these points were perpendicular to the axis of the lake. In general, a random walk model predicted the migration success rate of fish tracked through real lakes. However, for two lakes the simulated migration success exceeded that of actual success, suggesting that fish passing through these lakes were not adopting a random search strategy. We speculate that this is the result of either conflicting navigational cues which inhibit smolts from finding the lake outlet or that they temporarily suspend migration (e.g., to feed). Modelling predicted that for small lakes, directional swimming in short steps (ca. 100 m) followed by turns with very low variation from the direction of travel resulted in the highest migration success. For larger lakes, longer step lengths but also with low turn variation (simulated turning angle drawn from distributions of standard deviation 2 ° and 5 ° around a mean of 0 ° ) resulted in the highest migration success. We conclude that navigation in downstream migrating salmon smolts switches from rheotaxis in rivers to a random search tactic in lakes except where residual flow cues in some lakes prevent this, at times resulting in suboptimal navigation outcomes.

An investigation of an outbreak of Salmonella Typhimurium infections linked to cantaloupe – United States, 2022 - Sharon Seelman Federman; Erin Jenkins; Cullen Wilson; Arturo DeLaGarza; Colin Schwensohn; Benjamin Schneider; Johnson Nsubuga; Robert Literman; Allison Wellman; Brooke M. Whitney; Rebecca L. Bell; Kerri Harris-Garner; et al. (Food Control, 2024)

Ecotoxicological assessment of sanitary sewer overflows and rainfall dynamics offers insights into conditions for potential adverse ecological outcomes - Anu Kumar; Graeme E. Batley; Merrin Adams; Thao V. Nguyen; Bhanu Nidumolu; Huong Nguyen; Adrienne Gregg; Michele Cassidy; Colin H. Besley (Science of The Total Environment, 2024)

Inhibitory control mediates the effect of high intensity interval exercise on food choice - Madhronica Sardjoe; Sarah Aldred; Tanja Adam; Guy Plasqui; Jeffrey M. Brunstrom; Colin T. Dourish; Suzanne Higgs (Appetite, 2024)

Next generation risk assessment for occupational chemical safety – A real world example with sodium-2-hydroxyethane sulfonate - Adam Wood; Catherine Breffa; Caroline Chaine; Richard Cubberley; Matthew Dent; Joachim Eichhorn; Susann Fayyaz; Fabian A. Grimm; Jade Houghton; Reiko Kiwamoto; Predrag Kukic; MoungSook Lee; et al. (Toxicology, 2024)

How hot is too hot? Thermal tolerance, performance, and preference in juvenile mangrove whiprays, Urogymnus granulatus - Emily Higgins; Ian A. Bouyoucos; Adam T. Downie; Björn Illing; Ana P.B. Martins; Colin A. Simpfendorfer; Jodie L. Rummer (Journal of Thermal Biology, 2024)

Experimental and numerical studies on the vibration-based structural health monitoring of dimpled steel sheets with residual stresses - Scott Gohery; Ryan Adams; Mizan Ahmed; Qing Quan Liang; Navid Moslemi; Colin Burvill (Engineering Structures, 2024)

Genomic underpinnings of head and body shape in Arctic charr ecomorph pairs - Sam Fenton; Arne Jacobs; Colin W. Bean; Colin E. Adams; Kathryn R. Elmer (Molecular Ecology, 2024)
Across its Holarctic range, Arctic charr ( Salvelinus alpinus ) populations have diverged into distinct trophic specialists across independent replicate lakes. The major aspect of divergence between ecomorphs is in head shape and body shape, which are ecomorphological traits reflecting niche use. However, whether the genomic underpinnings of these parallel divergences are consistent across replicates was unknown but key for resolving the substrate of parallel evolution. We investigated the genomic basis of head shape and body shape morphology across four benthivore–planktivore ecomorph pairs of Arctic charr in Scotland. Through genome‐wide association analyses, we found genomic regions associated with head shape (89 SNPs) or body shape (180 SNPs) separately and 50 of these SNPs were strongly associated with both body and head shape morphology. For each trait separately, only a small number of SNPs were shared across all ecomorph pairs (3 SNPs for head shape and 10 SNPs for body shape). Signs of selection on the associated genomic regions varied across pairs, consistent with evolutionary demography differing considerably across lakes. Using a comprehensive database of salmonid QTLs newly augmented and mapped to a charr genome, we found several of the head‐ and body‐shape‐associated SNPs were within or near morphology QTLs from other salmonid species, reflecting a shared genetic basis for these phenotypes across species. Overall, our results demonstrate how parallel ecotype divergences can have both population‐specific and deeply shared genomic underpinnings across replicates, influenced by differences in their environments and demographic histories.

Migration patterns and navigation cues of Atlantic salmon post‐smolts migrating from 12 rivers through the coastal zones around the Irish Sea - Jessie Lilly; Hannele H. Honkanen; Jessica R. Rodger; Diego del Villar; Patrick Boylan; Amy Green; Diego Pereiro; Lorna Wilkie; Richard Kennedy; Andrea Barkley; Robert Rosell; Niall Ó. Maoiléidigh; et al. (Journal of Fish Biology, 2024)
The freshwater phase of the first seaward migration of juvenile Atlantic salmon ( Salmo salar ) is relatively well understood when compared with our understanding of the marine phase of their migration. In 2021, 1008 wild and 60 ranched Atlantic salmon smolts were tagged with acoustic transmitters in 12 rivers in England, Scotland, Northern Ireland and Ireland. Large marine receiver arrays were deployed in the Irish Sea at two locations: at the transition of the Irish Sea into the North Atlantic between Ireland and Scotland, and between southern Scotland and Northern Ireland, to examine the early phase of the marine migration of Atlantic salmon smolts. After leaving their natal rivers' post‐smolt migration through the Irish Sea was rapid with minimum speeds ranging from 14.03 to 38.56 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal river, to 9.69–39.94 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal estuary. Population minimum migration success through the study area was strongly correlated with the distance of travel, populations further away from the point of entry to the open North Atlantic exhibited lower migration success. Post‐smolts from different populations experienced different water temperatures on entering the North Atlantic. This was largely driven by the timing of their migration and may have significant consequences for feeding and ultimately survivorship. The influence of water currents on post‐smolt movement was investigated using data from previously constructed numerical hydrodynamic models. Modeled water current data in the northern Irish Sea showed that post‐smolts had a strong preference for migrating when the current direction was at around 283° (west‐north‐west) but did not migrate when exposed to strong currents in other directions. This is the most favorable direction for onward passage from the Irish Sea to the continental shelf edge current, a known accumulation point for migrating post‐smolts. These results strongly indicate that post‐smolts migrating through the coastal marine environment are: (1) not simply migrating by current following (2) engage in active directional swimming (3) have an intrinsic sense of their migration direction and (4) can use cues other than water current direction to orientate during this part of their migration.

Patterns and repeatability of multi‐ecotype assemblages of sympatric salmonids - Stephanie A. Blain; Dolph Schluter; Colin E. Adams; Per‐Arne Amundsen; Rune Knudsen; Louise Chavarie (Global Ecology and Biogeography, 2023)
Aim High repeatability among assemblages of closely related but ecologically distinct ecotypes implies predictability in evolution and assembly of communities. The conditions under which ecotype assemblages form predictably, and the reasons, have been little investigated. Here, we test whether repeatability declines as the number of ecotypes builds. Location Postglacial lakes with a circumboreal distribution. Time Period Data were extracted from studies published between 1982 and 2019. Major Taxa Studied Ecotype assemblages from two Salmonid genera – Salvelinus and Coregonus . Fish in postglacial lakes commonly occur as pairs of ecotypes, typically with a pelagic and a littoral/benthic form, but in Salvelinus and Coregonus , assemblages commonly contain multiple sympatric ecotypes. Methods We used a meta‐analysis of Salvelinus and Coregonus to empirically assess how repeatability varies across assemblages of two to seven ecotypes. We examined repeatability of use of broad niche categories as well as underlying phenotypic traits. Results Within Coregonus , repeatability across multi‐ecotype assemblages did not break down with the addition of a third or fourth ecotype. However, in Salvelinus , repeatability was largely absent and independent of the number of ecotypes. Repeatability of trait frequency distributions was absent in both genera, yet associations between trait means and niche categories were evident, especially in Coregonus . Main Conclusions These results show that repeatability can vary greatly between lineages; that repeatability need not break down as the number of ecotypes builds; and that high repeatability of broad niche categories may result despite marked differences in the underlying frequency distribution of trait means. These findings not only affirm the presence of repeatable ecotype assembly and early stages of divergence in postglacial fishes at a global scale, but also highlight variability among taxa and underlying phenotypic traits.

When are environmental DNA early detections of invasive species actionable? - Adam J. Sepulveda; Christine E. Dumoulin; Denise L. Blanchette; John McPhedran; Colin Holme; Nathan Whalen; Margaret E. Hunter; Christopher M. Merkes; Catherine A. Richter; Matthew E. Neilson; Wesley M. Daniel; Devin N. Jones; et al. (Journal of Environmental Management, 2023)

Arctic charr phenotypic responses to abrupt generational scale temperature change: an insight into how cold-water fish could respond to extreme climatic events - Oliver E. Hooker; Colin E. Adams; Louise Chavarie (Environmental Biology of Fishes, 2023)
Phenotypic plasticity, the ability of an organism to express multiple phenotypes in response to the prevailing environmental conditions without genetic change, may result in a response to anthropogenic environmental change. Given that increasing climate variability is predicted to pose a greater risk than directional climate change, we tested the effect of a water temperature differential of 4 °C on the Arctic charr phenotypic within a single generation. We demonstrate that Arctic charr phenotype can respond rapidly and markedly to an environmental temperature cue. The plastic response to different temperature regimes comprised a shift in the mean expressed phenotype but also coupled with a reduction in the between-individual phenotypic variation in the expressed head shape. The magnitude of shape difference between temperature conditions was cumulative over time but the rate of divergence diminished as fish became larger. Overall, individuals raised in the elevated temperature treatment expressed a phenotype analogous to a benthivorous ecotype of this species, rather than that of the parental pelagic feeding form. The response of cold-water freshwater species to temperature change is likely to be an interaction between the capacity of the organism for phenotypic plasticity, the mean speed of change in the environment, and the degree of short interval variation in the environment.

A Meta-Analysis of the Genome-Wide Association Studies on Two Genetically Correlated Phenotypes Suggests Four New Risk Loci for Headaches - Weihua Meng; Parminder S. Reel; Charvi Nangia; Aravind Lathika Rajendrakumar; Harry L. Hebert; Qian Guo; Mark J. Adams; Hua Zheng; Zen Haut Lu; Debashree Ray; Lesley A. Colvin; Colin N. A. Palmer; et al. (Phenomics, 2023)
Headache is one of the commonest complaints that doctors need to address in clinical settings. The genetic mechanisms of different types of headache are not well understood while it has been suggested that self-reported headache and self-reported migraine were genetically correlated. In this study, we performed a meta-analysis of genome-wide association studies (GWAS) on the self-reported headache phenotype from the UK Biobank and the self-reported migraine phenotype from the 23andMe using the Unified Score-based Association Test (metaUSAT) software for genetically correlated phenotypes ( N = 397,385). We identified 38 loci for headaches, of which 34 loci have been reported before and four loci were newly suggested. The LDL receptor related protein 1 ( LRP1 )— Signal Transducer and Activator of Transcription 6 ( STAT6 )— S hort chain D ehydrogenase / R eductase family 9C member 7 ( SDR9C7 ) region in chromosome 12 was the most significantly associated locus with a leading p value of 1.24 × 10 –62 of rs11172113. The One Cut homeobox 2 ( ONECUT2 ) gene locus in chromosome 18 was the strongest signal among the four new loci with a p value of 1.29 × 10 –9 of rs673939. Our study demonstrated that the genetically correlated phenotypes of self-reported headache and self-reported migraine can be meta-analysed together in theory and in practice to boost study power to identify more variants for headaches. This study has paved way for a large GWAS meta-analysis involving cohorts of different while genetically correlated headache phenotypes.

Combining acoustic telemetry with a mechanistic model to investigate characteristics unique to successful Atlantic salmon smolt migrants through a standing body of water - Jessie Lilly; Hannele M. Honkanen; Joseph M. McCallum; Matthew Newton; David M. Bailey; Colin E. Adams (Environmental Biology of Fishes, 2022)
The Atlantic salmon, Salmo salar Linnaeus 1758, is a charismatic, anadromous species that has faced dramatic declines throughout its range. There is currently a lack of information on the effect of free-standing bodies of water on a key life event, sea migration, for the species. This study extends our understanding in this area by combining acoustic telemetry with a correlated random walk model to try to examine potential morphological and behavioural factors that differentiate successful from unsuccessful migrants through Scotland’s largest lake. Consistent with other studies, we found that smolts experienced a high rate of mortality in the lake (~ 43%), with approximately 14% potentially predated upon by birds and 4% by Northern pike. Migration speed in the lake was slow (the mean minimum movement speed between centres of activity was 0.13 m/s), and pathways frequently deviated away from the outlet river. There was no evidence of a morphological or behavioural trait or migratory pathway that distinguished successful from unsuccessful smolts. This suggests that migration movement direction in the main body of Loch Lomond appeared to be random. This was further supported by the output of a correlated random walk model which closely resembled the pathway and migration speed and distance patterns displayed by successful migrants. However, once successful smolts came within ~2 km of the lake exit, a high proportion remained in this region prior to entering the River Leven. We suggest that this “goldilocks zone” is where directional cues become apparent to migrating fish. Future studies should combine random walk models with environmental variables to determine if external factors are driving the apparently random movement patterns exhibited by smolts in lakes.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Investigating the behaviour of Atlantic salmon ( Salmo salar L.) post‐smolts during their early marine migration through the Clyde Marine Region - Jessie Lilly; Hannele M. Honkanen; David M. Bailey; Colin W. Bean; Ruaidhri Forrester; Jessica R. Rodger; Colin E. Adams (Journal of Fish Biology, 2022)
It is thought that survival during migration is particularly poor for Atlantic salmon post‐smolts immediately after entry into sea and particularly in the estuarine environment. Nonetheless, there is currently a lack of information on Atlantic salmon post‐smolt movement behaviour in estuaries in the UK. This study used acoustic tagging to estimate loss rates and compare the behaviour of Atlantic salmon post‐smolts migrating from two distinctly different rivers draining into the Clyde Estuary, the River Endrick ( n = 145) and the Gryffe ( n = 102). Contrary to most literature, post‐smolts undertook rapid migrations through the estuary, potentially decreasing their exposure to predators/anthropogenic stressors and reducing their estimated loss rates (river: 1%–3% km –1 ; estuary: 0.20%–0.60% km –1 ). The low loss rates in the estuary occurred despite post‐smolts engaging in passive reversal movements with the tide upon entering the estuary, possibly allowing them more time to adapt to the increased salinity. Atlantic salmon post‐smolts from both the rivers used similar migration pathways exiting into the coastal marine zone during ebbing tide. This study provides novel information on the timing and migratory routes of Atlantic salmon post‐smolts in the Clyde Estuary that can ultimately be used to inform management decisions on how to assess and reduce the potential impacts of current natural and anthropogenic stressors. Temporal repeatability of this study over multiple years is required to determine if there is variation in the factors driving the migratory patterns and loss rates of smolts in this system.

PlanktoScope: Affordable Modular Quantitative Imaging Platform for Citizen Oceanography - Thibaut Pollina; Adam G. Larson; Fabien Lombard; Hongquan Li; David Le Guen; Sébastien Colin; Colomban de Vargas; Manu Prakash (Frontiers in Marine Science, 2022)
The oceans represent 97% of all water on Earth and contain microscopic, drifting life, plankton, which drives global biogeochemical cycles. A major hurdle in assessing marine plankton is the planetary scale of the oceans and the logistical and economic constraints associated with their sampling. This difficulty is reflected in the limited amount of scientifically equipped fleets and affordable equipment. Here we present a modular hardware/software open-source strategy for building a versatile, re-configurable imaging platform - the PlanktoScope - that can be adapted to a number of applications in aquatic biology and ecology. We demonstrate high-throughput quantitative imaging of laboratory and field plankton samples while enabling rapid device reconfiguration to match the evolving needs of the sampler. The presented versions of PlanktoScope are capable of autonomously imaging 1.7 ml per minute with a 2.8 µm/px resolution and can be controlled from any WiFi-enabled device. The PlanktoScope’s small size, ease of use, and low cost - under $1000 in parts - enable its deployment for customizable monitoring of laboratory cultures or natural micro-plankton communities. This also paves the way toward consistent and long-term measurement of plankton diversity by an international fleet of citizen vessels at the planetary scale.

Mapping risk to plant populations from short fire intervals via relationships between maturation period and environmental productivity - Carl R. Gosper; Ben P. Miller; Rachael V. Gallagher; Janine Kinloch; Richard van Dongen; Emma Adams; Sarah Barrett; Anne Cochrane; Sarah Comer; Lachlan McCaw; Russell G. Miller; Suzanne M. Prober; et al. (Plant Ecology, 2022)

Aging and white matter microstructure and macrostructure: a longitudinal multi-site diffusion MRI study of 1218 participants - Kurt G. Schilling; Derek Archer; Fang-Cheng Yeh; Francois Rheault; Leon Y. Cai; Colin Hansen; Qi Yang; Karthik Ramdass; Andrea T. Shafer; Susan M. Resnick; Kimberly R. Pechman; Katherine A. Gifford; et al. (Brain Structure and Function, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

An opinion piece: the evolutionary and ecological consequences of changing selection pressures on marine migration in Atlantic salmon - Colin E. Adams; Louise Chavarie; Jessica R. Rodger; Hannele M. Honkanen; Davide Thambithurai; Matthew P. Newton (Journal of Fish Biology, 2022)
There are strong signals that the selection forces favouring the expression of long‐distance sea migration by Atlantic salmon ( Salmo salar ) are changing. Unlike many other behavioural traits, the costs of migration are incurred before any fitness benefits become apparent to the migrant. The expression of this behaviour has thus been shaped by selection forces over multiple generations and cannot respond to short interval (within a single generation) environmental change as many other behavioural traits can. Here we provide a framework to examine the evolutionary and ecological consequences of a sustained increase in migration cost. We argue that Atlantic salmon may have entered an evolutionary trap , where long‐distance sea migration has become maladaptive because of shifting environmental conditions. We predict that if higher migration costs (affecting survivorship and ultimately fitness) persist, then shifting selection pressures will result in continuing declines in population size. We suggest, however, that in some populations there is demonstrable capacity for evolutionary rescue responses within the species which is to be found in the variation in the expression of migration. Under a scenario of low to moderate change in the selection forces that previously promoted migration, we argue that disruptive, sex‐based selection would result in partial migration, where females retain sea migration but with anadromy loss predominantly in males. With more acute selection forces, anadromy may be strongly selected against, under these conditions both sexes may become freshwater resident. We suggest that as the migration costs appear to be higher in catchments with standing waters, then this outcome is more likely in such systems. We also speculate that as a result of the genetic structuring in this species, not all populations may have the capacity to respond adequately to change. The consequences of this for the species and its management are discussed.

A comparison of trends in population size and life history features of Atlantic salmon (Salmo salar) and anadromous and non-anadromous Brown trout (Salmo trutta) in a single catchment over 116 years - Colin E. Adams; Hannele M. Honkanen; Ellen Bryson; Isabel E. Moore; Malcolm MacCormick; Jennifer A. Dodd (Hydrobiologia, 2022)
We use a long time series of catch abundance from a recreational fishery over 116 years to look for population trends in Atlantic salmon, and anadromous (sea trout) and non-anadromous (brown) trout for a single catchment, Loch Lomond, west central Scotland. Year strongly predicted variation in catches but catch effort did not meaningfully increase explained variation. Salmon showed periods of increasing and decreasing trends, for sea trout and brown trout there was an overall declining trend. Since 1952, Lomond salmon population trends differed from both wider Scotland and southern Europe, indicating that the Lomond population is partially buffered from drivers of change in salmon populations more widely. In contrast Lomond sea trout showed a similar declining trend to that of populations from the wider west of Scotland over this period. The Lomond populations showed some evidence of shorter-term cycling patterns; the drivers for which are unknown. Body size in salmon and sea trout declined but increased in brown trout; salmon returned to freshwater later, and the relative proportion of all caught trout that were anadromous increased across the time series. This study shows a long and protracted period of fundamental change to populations of these two species over 116 years.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

High-Resolution Spatiotemporal Dynamics of Harmful Algae in the Indian River Lagoon (Florida)—A Case Study of Aureoumbra lagunensis, Pyrodinium bahamense, and Pseudo-nitzschia - Cary B. Lopez; Charles L. Tilney; Eric Muhlbach; Josée N. Bouchard; Maria Célia Villac; Karen L. Henschen; Laura R. Markley; Stephanie Keller Abbe; Sugandha Shankar; Colin P. Shea; Leanne Flewelling; Matthew Garrett; et al. (Frontiers in Marine Science, 2021)
The Indian River Lagoon (IRL), located on the east coast of Florida, is a complex estuarine ecosystem that is negatively affected by recurring harmful algal blooms (HABs) from distinct taxonomic/functional groups. Enhanced monitoring was established to facilitate rapid quantification of three recurrent bloom taxa, Aureoumbra lagunensis , Pyrodinium bahamense , and Pseudo-nitzschia spp., and included corroborating techniques to improve the identification of small-celled nanoplankton (<10 μm in diameter). Identification and enumeration of these target taxa were conducted during 2015–2020 using a combination of light microscopy and species-specific approaches, specifically immunofluorescence flow cytometry as well as a newly developed qPCR assay for A. lagunensis presented here for the first time. An annual bloom index (ABI) was established for each taxon based on occurrence and abundance data. Blooms of A. lagunensis (>2 × 10 8 cells L –1 ) were observed in all 6 years sampled and across multiple seasons. In contrast, abundance of P. bahamense , largely driven by the annual temperature cycle that moderates life cycle transitions and growth, displayed a strong seasonal pattern with blooms (10 5 –10 7 cells L –1 ) generally developing in early summer and subsiding in autumn. However, P. bahamense bloom development was delayed and abundance was significantly lower in years and locations with sustained A. lagunensis blooms. Pseudo-nitzschia spp. were broadly distributed with sporadic bloom concentrations (reaching 10 7 cells L –1 ), but with minimal concentrations of the toxin domoic acid detected (<0.02 μg L –1 ). In summer 2020, multiple monitoring tools characterized a novel nano-cyanobacterium bloom (reaching 10 9 cells L –1 ) that coincided with a decline in A. lagunensis and persisted into autumn. Statistical and time-series analyses of this spatiotemporally intensive dataset highlight prominent patterns in variability for some taxa, but also identify challenges of characterizing mechanisms underlying more episodic yet persistent events. Nevertheless, the intersect of temperature and salinity as environmental proxies proved to be informative in delineating niche partitioning, not only in the case of taxa with long-standing data sets but also for seemingly unprecedented blooms of novel nanoplanktonic taxa.

Continental‐scale acoustic telemetry and network analysis reveal new insights into stock structure - Elodie J. I. Lédée; Michelle R. Heupel; Matthew D. Taylor; Robert G. Harcourt; Fabrice R. A. Jaine; Charlie Huveneers; Vinay Udyawer; Hamish A. Campbell; Russell C. Babcock; Xavier Hoenner; Adam Barnett; Matias Braccini; et al. (Fish and Fisheries, 2021)
Delineation of population structure (i.e. stocks) is crucial to successfully manage exploited species and to address conservation concerns for threatened species. Fish migration and associated movements are key mechanisms through which discrete populations mix and are thus important determinants of population structure. Detailed information on fish migration and movements is becoming more accessible through advances in telemetry and analysis methods however such information is not yet used systematically in stock structure assessment. Here, we described how detections of acoustically tagged fish across a continental‐scale array of underwater acoustic receivers were used to assess stock structure and connectivity in seven teleost and seven shark species and compared to findings from genetic and conventional tagging. Network analysis revealed previously unknown population connections in some species, and in others bolstered support for existing stock discrimination by identifying nodes and routes important for connectivity. Species with less variability in their movements required smaller sample sizes (45–50 individuals) to reveal useful stock structure information. Our study shows the power of continental‐scale acoustic telemetry networks to detect movements among fishery jurisdictions. We highlight methodological issues that need to be considered in the design of acoustic telemetry studies for investigating stock structure and the interpretation of the resulting data. The advent of broad‐scale acoustic telemetry networks across the globe provides new avenues to understand how movement informs population structure and can lead to improved management.

Low‐intensity frequent fires in coniferous forests transform soil organic matter in ways that may offset ecosystem carbon losses - Adam F. A. Pellegrini; Anthony C. Caprio; Katerina Georgiou; Colin Finnegan; Sarah E. Hobbie; Jeffery A. Hatten; Robert B. Jackson (Global Change Biology, 2021)
The impact of shifting disturbance regimes on soil carbon (C) storage is a key uncertainty in global change research. Wildfires in coniferous forests are becoming more frequent in many regions, potentially causing large C emissions. Repeated low‐intensity prescribed fires can mitigate wildfire severity, but repeated combustion may decrease soil C unless compensatory responses stabilize soil organic matter. Here, we tested how 30 years of decadal prescribed burning affected C and nitrogen (N) in plants, detritus, and soils in coniferous forests in the Sierra Nevada mountains, USA. Tree basal area and litter stocks were resilient to fire, but fire reduced forest floor C by 77% (−36.4 Mg C/ha). In mineral soils, fire reduced C that was free from minerals by 41% (−4.4 Mg C/ha) but not C associated with minerals, and only in depths ≤ 5 cm. Fire also transformed the properties of remaining mineral soil organic matter by increasing the proportion of C in a pyrogenic form (from 3.2% to 7.5%) and associated with minerals (from 46% to 58%), suggesting the remaining soil C is more resistant to decomposition. Laboratory assays illustrated that fire reduced microbial CO 2 respiration rates by 55% and the activity of eight extracellular enzymes that degrade cellulosic and aromatic compounds by 40–66%. Lower decomposition was correlated with lower inorganic N (−49%), especially ammonium, suggesting N availability is coupled with decomposition. The relative increase in forms of soil organic matter that are resistant to decay or stabilized onto mineral surfaces, and the associated decline in decomposition suggest that low‐intensity fires may promote mineral soil C storage in pools with long mean residence times in coniferous forests.

Pandora: 4-D White Matter Bundle Population-Based Atlases Derived from Diffusion MRI Fiber Tractography - Colin B Hansen; Qi Yang; Ilwoo Lyu; Francois Rheault; Cailey Kerley; Bramsh Qamar Chandio; Shreyas Fadnavis; Owen Williams; Andrea T. Shafer; Susan M. Resnick; David H. Zald; Laurie E Cutting; et al. (Neuroinformatics, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Techniques for In Vivo Measurement of Ligament and Tendon Strain: A Review - Qiang Zhang; Naomi C. Adam; S. H. Hosseini Nasab; William R. Taylor; Colin R. Smith (Annals of Biomedical Engineering, 2021)
The critical clinical and scientific insights achieved through knowledge of in vivo musculoskeletal soft tissue strains has motivated the development of relevant measurement techniques. This review provides a comprehensive summary of the key findings, limitations, and clinical impacts of these techniques to quantify musculoskeletal soft tissue strains during dynamic movements. Current technologies generally leverage three techniques to quantify in vivo strain patterns, including implantable strain sensors, virtual fibre elongation, and ultrasound. (1) Implantable strain sensors enable direct measurements of tissue strains with high accuracy and minimal artefact, but are highly invasive and current designs are not clinically viable. (2) The virtual fibre elongation method tracks the relative displacement of tissue attachments to measure strains in both deep and superficial tissues. However, the associated imaging techniques often require exposure to radiation, limit the activities that can be performed, and only quantify bone-to-bone tissue strains. (3) Ultrasound methods enable safe and non-invasive imaging of soft tissue deformation. However, ultrasound can only image superficial tissues, and measurements are confounded by out-of-plane tissue motion. Finally, all in vivo strain measurement methods are limited in their ability to establish the slack length of musculoskeletal soft tissue structures. Despite the many challenges and limitations of these measurement techniques, knowledge of in vivo soft tissue strain has led to improved clinical treatments for many musculoskeletal pathologies including anterior cruciate ligament reconstruction, Achilles tendon repair, and total knee replacement. This review provides a comprehensive understanding of these measurement techniques and identifies the key features of in vivo strain measurement that can facilitate innovative personalized sports medicine treatment.

Volatile Organic Compounds as Insect Repellents and Plant Elicitors: an Integrated Pest Management (IPM) Strategy for Glasshouse Whitefly (Trialeurodes vaporariorum) - Niall J.A. Conboy; Thomas McDaniel; David George; Adam Ormerod; Martin Edwards; Paul Donohoe; Angharad M. R Gatehouse; Colin R. Tosh (Journal of Chemical Ecology, 2020)
The glasshouse whitefly ( Trialeurodes vaporariorum Westwood) is a polyphagous arthropod pest that is of particular detriment to glasshouse grown tomato ( Solanum lycopersicum ) across temperate regions of the world. Control of whiteflies with synthetic pesticides has resulted in the evolution of resistant genotypes and a reduction in natural enemies, thus highlighting the need for environmentally sound control strategies. Volatile organic compounds (VOCs) offer an environmentally benign alternative to synthetic chemical sprays and this study explored the use of VOCs as insect repellents and plant defence elicitors to control whiteflies on tomato in a commercial glasshouse setting. Limonene in the form of a volatile dispenser system was found to successfully repel whitefly from the target crop and increased fruit yield by 32% during a heavy whitefly infestation. Analysis of tomato herbivore induced plant volatiles (HIPVs) led us to select methyl salicylate (MeSA) as the plant elicitor and application of MeSA to un-infested tomato plants was found to successfully reduce whitefly population development and increase yield by 11%, although this difference was marginally statistically significant. Combination of these two methods was also effective but whitefly abundance in combined plots was similar to the standalone limonene treatment across the course of the experiment. All of the VOC based control methods we used had a negative impact on whitefly performance, with more pronounced effects during the first few weeks of infestation. In subsequent laboratory experiments, we found elevated peroxidase (POD) activity and a significant increase in TPX1 and PR1 transcripts in MeSA treated plants. This led us to deduce that MeSA immediately induced plant defences, rather than priming them. We did however see evidence for residual priming, as plants treated with MeSA and infested with whiteflies produced significantly higher levels of POD activity than whitefly infestation alone. Despite the fact that our treatments failed to synergise, our methods can be optimised further, and the effectiveness of the standalone treatments is promising for future studies. In particular, our repellent limonene dispensers were extremely effective at deterring whiteflies and offer a low economic cost and easy to implement whitefly control option. The methods we have used here could be incorporated into current integrated pest management (IPM) systems, a sustainable approach to pest control which will be central to our efforts to manage whitefly populations under glass in the future.

Correction to: The Capacity of Generic Musculoskeletal Simulations to Predict Knee Joint Loading Using the CAMS-Knee Datasets - Zohreh Imani Nejad; Khalil Khalili; Seyyed Hamed Hosseini Nasab; Pascal Schütz; Philipp Damm; Adam Trepczynski; William R. Taylor; Colin R. Smith (Annals of Biomedical Engineering, 2020)

The Capacity of Generic Musculoskeletal Simulations to Predict Knee Joint Loading Using the CAMS-Knee Datasets - Zohreh Imani Nejad; Khalil Khalili; Seyyed Hamed Hosseini Nasab; Pascal Schütz; Philipp Damm; Adam Trepczynski; William R. Taylor; Colin R. Smith (Annals of Biomedical Engineering, 2020)
Musculoskeletal models enable non-invasive estimation of knee contact forces (KCFs) during functional movements. However, the redundant nature of the musculoskeletal system and uncertainty in model parameters necessitates that model predictions are critically evaluated. This study compared KCF and muscle activation patterns predicted using a scaled generic model and OpenSim static optimization tool against in vivo measurements from six patients in the CAMS-knee datasets during level walking and squatting. Generally, the total KCFs were under-predicted (RMS: 47.55%BW, R 2 : 0.92) throughout the gait cycle, but substiantially over-predicted (RMS: 105.7%BW, R 2 : 0.81) during squatting. To understand the underlying etiology of the errors, muscle activations were compared to electromyography (EMG) signals, and showed good agreement during level walking. For squatting, however, the muscle activations showed large descrepancies especially for the biceps femoris long head. Errors in the predicted KCF and muscle activation patterns were greatest during deep squat. Hence suggesting that the errors mainly originate from muscle represented at the hip and an associated muscle co-contraction at the knee. Furthermore, there were substaintial differences in the ranking of subjects and activities based on peak KCFs in the simulations versus measurements. Thus, future simulation study designs must account for subject-specific uncertainties in musculoskeletal predictions.

A phenotypically plastic magic trait promoting reproductive isolation in sticklebacks? - Monica V. Garduno-Paz; Felicity A. Huntingford; Sean Garrett; Colin E. Adams (Evolutionary Ecology, 2020)
This study identifies one possible mechanism whereby gene flow is interrupted in populations undergoing evolutionary divergence in sympatry; this is an important issue in evolutionary biology that remains poorly understood. Variation in trophic morphology was induced in three-spined stickleback by exposing them from an early age either to large benthic or to small pelagic prey. At sexual maturity, females given a choice between two breeding males, showed positive assortative mate choice for males raised on the same diet as themselves. The data indicate that this was mediated through a preference for males with trophic morphology similar to that of fish with which the females were familiar (from their pre-testing holding tanks). In trials where the female did not choose the most familiar male, the evidence suggests that either she had difficulty discriminating between two similar males or was positively choosing males with more extreme morphologies (more benthic-like or pelagic-like). This study has shown for the first time that expression of a plastic trait induced at an early age, not only results in specialisation for local foraging regimes but can also play a significant role in mate choice. This is equivalent to an environmentally induced, plastic version of the “magic traits” that promote ecologically-driven divergence in sympatry, hence the proposed descriptor “plastic magic trait”.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Differential selection pressures result in a rapid divergence of donor and refuge populations of a high conservation value freshwater fish Coregonus lavaretus (L.) - J. Peter Koene; Marco Crotti; Kathryn R. Elmer; Colin E. Adams (Evolutionary Ecology, 2019)

C 4 anatomy can evolve via a single developmental change - Marjorie R. Lundgren; Luke T. Dunning; Jill K. Olofsson; Jose J. Moreno‐Villena; Jacques W. Bouvier; Tammy L. Sage; Roxana Khoshravesh; Stefanie Sultmanis; Matt Stata; Brad S. Ripley; Maria S. Vorontsova; Guillaume Besnard; et al. (Ecology Letters, 2019)
C 4 photosynthesis is a complex trait that boosts productivity in warm environments. Paradoxically, it evolved independently in numerous plant lineages, despite requiring specialised leaf anatomy. The anatomical modifications underlying C 4 evolution have previously been evaluated through interspecific comparisons, which capture numerous changes besides those needed for C 4 functionality. Here, we quantify the anatomical changes accompanying the transition between non‐C 4 and C 4 phenotypes by sampling widely across the continuum of leaf anatomical traits in the grass Alloteropsis semialata . Within this species, the only trait that is shared among and specific to C 4 individuals is an increase in vein density, driven specifically by minor vein development that yields multiple secondary effects facilitating C 4 function. For species with the necessary anatomical preconditions, developmental proliferation of veins can therefore be sufficient to produce a functional C 4 leaf anatomy, creating an evolutionary entry point to complex C 4 syndromes that can become more specialised.

Unravelling the complexity of magma plumbing at Mount St. Helens: a new trace element partitioning scheme for amphibole - Madeleine C. S. Humphreys; George F. Cooper; Jing Zhang; Matthew Loewen; Adam J. R. Kent; Colin G. Macpherson; Jon P. Davidson (Contributions to Mineralogy and Petrology, 2019)

RADseq and mate choice assays reveal unidirectional gene flow among three lamprey ecotypes despite weak assortative mating: Insights into the formation and stability of multiple ecotypes in sympatry - John B. Hume; Hans Recknagel; Colin W. Bean; Colin E. Adams; Barbara K. Mable (Molecular Ecology, 2018)
Adaptive divergence with gene flow often results in complex patterns of variation within taxa exhibiting substantial ecological differences among populations. One example where this may have occurred is the parallel evolution of freshwater‐resident nonparasitic lampreys from anadromous‐parasitic ancestors. Previous studies have focused on transitions between these two phenotypic extremes, but here, we considered more complex evolutionary scenarios where an intermediate freshwater form that remains parasitic is found sympatrically with the other two ecotypes. Using population genomic analysis (restriction‐associated DNA sequencing), we found that a freshwater‐parasitic ecotype was highly distinct from an anadromous‐parasitic form ( Q lake‐P = 96.8%, F st = 0.154), but that a freshwater‐nonparasitic form was almost completely admixed in Loch Lomond, Scotland. Demographic reconstructions indicated that both freshwater populations likely derived from a common freshwater ancestor. However, while the nonparasitic ecotype has experienced high levels of introgression from the anadromous‐parasitic ecotype ( Q anad‐P = 37.7%), there is no evidence of introgression into the freshwater‐parasitic ecotype. Paradoxically, mate choice experiments predicted high potential for gene flow: Males from all ecotypes were stimulated to spawn with freshwater‐parasitic females, which released gametes in response to all ecotypes. Differentially fixed single nucleotide polymorphisms identified genes associated with growth and development, which could possibly influence the timing of metamorphosis, resulting in significant ecological differences between forms. This suggests that multiple lamprey ecotypes can persist in sympatry following shifts in adaptive peaks, due to environmental change during their repeated colonization of post‐glacial regions, followed by periods of extensive gene flow among such diverging populations.

Counterintuitive migration patterns by Atlantic salmon Salmo salar smolts in a large lake - Hannele M. Honkanen; Jessica R. Rodger; Alastair Stephen; Keith Adams; James Freeman; Colin E. Adams (Journal of Fish Biology, 2018)
What little is known about the seaward migration of Salmo salar smolt migration through standing waters indicates that it is both slow and results in high mortality rates, compared with riverine migration. This may be partly because smolts in lakes need to swim more actively and require more complex directional cues than they do in rivers. In this telemetry study of smolt migration through Loch Lomond, S. salar smolts made repeated movements in directions away from the outflowing river, which considerably increased migration time.

Evolution in action: allopatry, variable diversity and a stepping-stone model of migration among populations of the freshwater bivalve Triplodon corrugatus from the north-eastern Amazon - Guilherme da Cruz Santos-Neto; Ismael Sander da Silva Nunes; Colin Robert Beasley; Adam Rick Bessa Silva; Cleidson Paiva Gomes; Claudia Helena Tagliaro (Hydrobiologia, 2018)

Geographically distributed hybrid testing & collaboration between geotechnical centrifuge and structures laboratories - Mobin Ojaghi; Ignacio Lamata Martínez; Matt S. Dietz; Martin S. Williams; Anthony Blakeborough; Adam J. Crewe; Colin A. Taylor; S. P. Gopal Madabhushi; Stuart K. Haigh (Earthquake Engineering and Engineering Vibration, 2018)

Freshwater fisheries ecologyEdited by John F.Craig, 2015, Wiley‐Blackwell, Oxford, UK. ISBN‐13: 978‐1‐118‐39442‐7; (Hbk); GBP 79.50 EUR 95.40 USD 125.00 (hardcover); GBP 75.50 EUR 85.99 (electronic). pp.920, numerous figures. Subject, country, fish, species and author indices. - Colin E Adams (Fish and Fisheries, 2018)

Divergent functional traits in three sympatric Arctic charr Salvelinus alpinus morphs are not coupled with the age of the lineage divergence - Carolyn Bryce; Alicia Fraser; Rune Knudsen; Ron Greer; Colin Adams (Hydrobiologia, 2016)

The role of Salvelinus in contemporary studies of evolution, trophic ecology and anthropogenic change - Rune Knudsen; Anders Klemetsen; Sergey Alekseyev; Colin E. Adams; Michael Power (Hydrobiologia, 2016)

Proceedings of the second international molecular pathological epidemiology (MPE) meeting - Shuji Ogino; Peter T. Campbell; Reiko Nishihara; Amanda I. Phipps; Andrew H. Beck; Mark E. Sherman; Andrew T. Chan; Melissa A. Troester; Adam J. Bass; Kathryn C. Fitzgerald; Rafael A. Irizarry; Karl T. Kelsey; et al. (Cancer Causes & Control, 2015)

Multiplex species-specific PCR identification of native and non-native oysters (Crassostrea) in Brazil: a useful tool for application in oyster culture and stock management - Mauro André Damasceno Melo; Adam Rick Bessa da Silva; Colin Robert Beasley; Claudia Helena Tagliaro (Aquaculture International, 2013)

Discrete foraging niches promote ecological, phenotypic, and genetic divergence in sympatric whitefish (Coregonus lavaretus) - Anna Siwertsson; Rune Knudsen; Kim Præbel; Colin E. Adams; Jason Newton; Per-Arne Amundsen (Evolutionary Ecology, 2013)

The impact of increased food availability on survival of a long‐distance migratory bird - Adam M. Seward; Colin M. Beale; Lucy Gilbert; T. Hefin Jones; Robert J. Thomas (Ecology, 2013)
Temperature‐, rainfall‐ and habitat‐driven change in food availability is one likely mechanism by which anthropogenic factors may affect animal population dynamics and species distributions. Long‐distance migratory birds must synchronize their migrations with food availability at locations hundreds or thousands of kilometers apart, so changes in the overall abundance of food or the phenology of peaks in food availability may be critical factors influencing annual survival. In this study we used experimental food supplementation at a breeding site to examine and compare the impact of changing food supply on annual survival of adult migratory birds and their offspring. We provided supplemental food to Northern Wheatears ( Oenanthe oenanthe ) breeding on Fair Isle, UK, to infer the sensitivity of annual survival to increases in natural food availability. Food‐supplemented wheatears exhibited higher rates of annual survival than control wheatears, and the strength of this effect varied with age. Food supplementation led to 1.56 times higher annual survival of juveniles and 1.22 times higher survival of adults. Survival of juveniles was related to their own food availability as fledglings, but not to whether their parents were food‐supplemented or unfed control adults. This increased survival, combined with increased breeding productivity associated with food supplementation, implies that an increase in natural food availability, of the magnitude simulated in our experiment, would increase the population growth rate of wheatears on Fair Isle from approximately λ = 0.93 (a contracting population) to λ = 1.14 (an expanding population).

Amyloid Precursor Protein Expression Modulates Intestine Immune Phenotype - Kendra L. Puig; Adam J. Swigost; Xudong Zhou; Mary Ann Sens; Colin K. Combs (Journal of Neuroimmune Pharmacology, 2012)

Herbivore-Induced Changes in Tomato (Solanum lycopersicum) Primary Metabolism: A Whole Plant Perspective - Adam D. Steinbrenner; Sara Gómez; Sonia Osorio; Alisdair R. Fernie; Colin M. Orians (Journal of Chemical Ecology, 2011)

Temporal stability of niche use exposes sympatric Arctic charr to alternative selection pressures - Rune Knudsen; Anna Siwertsson; Colin E. Adams; Monica Garduño-Paz; Jason Newton; Per-Arne Amundsen (Evolutionary Ecology, 2011)

Net pelagic heterotrophy in mesotrophic and oligotrophic basins of a large, temperate lake - Adrian M. Bass; Susan Waldron; Tom Preston; Colin E. Adams (Hydrobiologia, 2010)

A perspective on Salvelinus research - Colin Adams; Eva Brännäs; Brian Dempson; Rune Knudsen; Ian McCarthy; Michael Power; Ian Winfield (Hydrobiologia, 2010)

Discrete prey availability promotes foraging segregation and early divergence in Arctic charr, Salvelinus alpinus - Mónica V. Garduño-Paz; Colin E. Adams (Hydrobiologia, 2010)

Role of epithelial-to-mesenchymal transition (EMT) in drug sensitivity and metastasis in bladder cancer - David J. McConkey; Woonyoung Choi; Lauren Marquis; Frances Martin; Michael B. Williams; Jay Shah; Robert Svatek; Aditi Das; Liana Adam; Ashish Kamat; Arlene Siefker-Radtke; Colin Dinney (Cancer and Metastasis Reviews, 2009)

Ecological assessment to detect imminent change in coral reefs of Admiral Cockburn Land and Sea National Park, Turks and Caicos Islands - Angela Dikou; Colin Ackerman; Carly Banks; Alex Dempsey; Michael Fox; Meagan Gins; Patricia Hester; Adam Parnes; Stephanie Roach; Jessica Rohde; Cliff Spital; Mackai Tapleshay; et al. (Marine Ecology, 2009)
Coral reefs of the Turks and Caicos Islands (TCIs) (Caribbean Sea) constitute some of the few pristine coral reef systems in the world and play a crucial role in the islands’ economy because they support rich fisheries catches and tourism development. Ambitious development plans involving increase in fishing and tourism pressures are about to bring changes in coastal zone resources of the TCIs associated with increased sediments and nutrients and reduced predation by herbivorous fish on coral reefs. Understanding change is critical when attempting to protect the resources that these coral reefs support and to adopt proper management strategies. Yet, an environmental assessment program to detect imminent human‐induced changes on the surrounding reefs of the TCIs is lacking. Thus, (i) we obtained baseline data on benthic composition and coral community structure at seven reef sites of representative reefs of the TCIs within the Admiral Cockburn Land and Sea National Park (ACLSNP) of South Caicos Island and (ii) performed a priori statistical power analysis to calculate replication requirements for safely and confidently detecting small (δ = 0.1), medium (δ = 0.3), and large (δ = 0.5) effect sizes for a number of relevant to anticipated changes, univariate, benthic indices and for power β = 0.95. The platforms of the margin reefs studied (9–12 m depth) appeared rather variable regarding benthic composition but quite homogeneous regarding hard coral community structure. Mean percent cover of algal functional groups was 0.1 ± 0.3 (mean ± sd) percent for coralline algae and Halimeda , 0.1 ± 0.6 (mean ± sd) percent for macroalgae, 21.7 ± 33 (mean ± sd) percent for turf algae and 4.8 ± 4.0 (mean ± sd) percent for hard coral cover. The dominant benthic component, however, was carbonate substrate (mean ± sd = 30.4 ± 34.3), thus indicating an accreting reef framework. Mean hard coral density, colony size and recruit density were 5.5 ± 1.8 (mean ± sd) corals per 20‐m line transect, 13.0 ± 2.3 (mean ± sd) cm maximum colony diameter, and 1.3 ± 1.4 (mean ± sd) recruits per square foot, respectively. Due to high natural variance, hard coral colony size and density were practically the most sensitive indices in detecting even small size changes on benthos. Also, the geometric mean of log‐transformed colony size‐frequency distributions of the most abundant hard coral taxa, i.e. Montastrea annularis , Agaricia spp., Siderastrea spp. and Porites asteroides were practically sensitive for the same purpose. We hope that the study will optimize the spatial component of a necessary environmental impact assessment program on coral reefs of the TCIs once the natural spatial variability of the system has been assessed and sensitive, benthic, univariate indices have been identified for representative reference coral reef sites of the TCIs.

Threatened fishes of the world: Menidia riojai Solórzano and López 1965 (Atheriniformes: Atherinopsidae) - J. Fernando Méndez-Sánchez; Mónica V. Garduño-Paz; M. de Lourdes Ruíz-Gómez; Oswaldo Hernández-Gallegos; Colin E. Adams (Environmental Biology of Fishes, 2008)

The implications of a feelings‐based approach to fish welfare: a reply to Arlinghaus et al. - Felicity Huntingford; Colin Adams; Victoria A. Braithwaite; Sunil Kadri; Tom G. Pottinger; Peter Sandoe; James F. Turnbull (Fish and Fisheries, 2007)
The welfare of fish is a topic of increasing debate touching on a number of complex scientific and ethical issues and constructive dialogue between groups with differing approaches to the topic requires mutual understanding from both perspectives. In a recent review aimed at stimulating debate on this topic, Arlinghaus et al. (2007) explore the question of fish welfare in the particular context of recreational angling, by means of a critique of a review of fish welfare in general written by ourselves ( Huntingford et al. 2006 ). We entirely agree with the desirability of debate on this topic and recognize a number of valuable qualities in the commentary by Arlinghaus et al. However, we argue that the critique has some serious flaws. In the first place, by rejecting a feelings‐based approach to welfare, it fails to address the aspect of welfare that is at the heart of much legitimate public concern. Secondly, while advocating an objective, scientific approach to fish welfare, Arlinghaus et al. fail to present their own agenda (that recreational angling is morally acceptable) in a transparent way. Thirdly, they seriously misrepresent the position taken in Huntingford et al. (2006) on a number of important issues. In this reply, we address these points and then discuss briefly the areas of agreement and constructive disagreement between the two reviews.

Increasing abundance and diversity in the moth assemblage of east Loch Lomondside, Scotland over a 35 year period - Nabeil K. G. Salama; John T. Knowler; Colin E. Adams (Journal of Insect Conservation, 2007)

Does Breeding Site Fidelity Drive Phenotypic and Genetic Sub-Structuring of a Population of Arctic Charr? - Colin E. Adams; Deborah J. Hamilton; Ian Mccarthy; Alastair J. Wilson; Alan Grant; Gavin Alexander; Susan Waldron; Sigurdur S. Snorasson; Moira M. Ferguson; Skuli Skúlason (Evolutionary Ecology, 2006)

Empirical Modelling of the Population Dynamics of a Small Population of the Threespine Stickleback, Gasterosteus aculeatus - Robert J. Wootton; Colin E. Adams; Martin J. Attrill (Environmental Biology of Fishes, 2005)

Y chromosome haplogroups of elite Ethiopian endurance runners - Colin N. Moran; Robert A. Scott; Susan M. Adams; Samantha J. Warrington; Mark A. Jobling; Richard H. Wilson; William H. Goodwin; Evelina Georgiades; Bezabhe Wolde; Yannis P. Pitsiladis (Human Genetics, 2004)

The functional significance of inherited differences in feeding morphology in a sympatric polymorphic population of Arctic charr - Colin E. Adams; Felicity A. Huntingford (Evolutionary Ecology, 2002)

Size heterogeneity can reduce aggression and promote growth in Atlantic salmon parr - Colin Adams; Felicity Huntingford; Jimmy Turnbull; Steve Arnott; Aly Bell (Aquaculture International, 2000)

Oxygenation and perfusion of rabbit tibialis anterior muscle subjected to different patterns of electrical stimulation - Adam R. Greenbaum; Jonathan C. Jarvis; Daniel O'Hare; Sanjiv Manek; Colin J. Green; John R. Pepper; C. Peter Winlove; Stanley Salmons (Journal of Muscle Research and Cell Motility, 2000)

Book review and notices - M. Beveridge; M. Jobling; Colin E. Adams; R. Williamson (Aquaculture International, 1996)